IMPLEMENTING SENSORY BIN PLAY TO IMPROVE FINE MOTOR SKILLS OF 4–5-YEAR-OLD KINDERGARTEN CHILDREN AT KARTINI WANGKAL - Agustin, Chintya; Ahmad Afandi; Rizki Sevi Triana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to optimize the fine motor skills of children aged 4–5 years through sensory bin play activities. The research employed Classroom Action Research conducted in two cycles, consisting of planning, action implementation, observation, and reflection stages, with 15 children from TK Kartini Wangkal, Probolinggo Regency as the research participants. Data were collected through structured observations using a fine motor skills assessment sheet that included indicators of hand–eye coordination as well as finger strength and flexibility. Data analysis was conducted using descriptive quantitative methods with percentage techniques. The results showed an improvement in children’s fine motor skills from Cycle I, which was dominated by the Developing category (75%) and the Developing as Expected category (25%), to the Developing as Expected (67%) and Very Well Developed (33%) categories in Cycle II. These findings indicate that sensory bin play activities are effective in optimizing fine motor skills in kindergarten-aged children.